2015
DOI: 10.3406/revec.2015.1829
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the uses of gorse in native and invaded regions : what are the impacts on its dynamics and management ?

Abstract: Évolution des usages de l'ajonc dans ses régions d'origine ou envahies : quels impacts sur sa dynamique et sa gestion ?-L'introduction et l'expansion géographique des espèces invasives, comme leur régression, suivent souvent des processus où le rôle de l'Homme est central. C'est le cas de l'Ajonc d'Europe (Ulex europaeus) qui a été introduit volontairement dans plus de 30 pays différents, et est considéré comme l'une des « 100 of the world's worst invasive species » par l'UICN. Dans sa zone d'origine (principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The similarity of the values of biomass mean annual increment (MAI) in gorsedominated communities in the sample plots of this study with those reported for native Western Europe stands [154] seems consistent with similar climatic conditions and history of land use and disturbance in those habitats [155]. However, data reported by Carswell et al [49] for this species in treeless stands in New Zealand show high growth maintained even beyond 15 years, which could be related to a niche shift, or simply due to the short time interval explored.…”
Section: Biomass Accumulation and Mean Annual Increment (Mai)supporting
confidence: 84%
“…The similarity of the values of biomass mean annual increment (MAI) in gorsedominated communities in the sample plots of this study with those reported for native Western Europe stands [154] seems consistent with similar climatic conditions and history of land use and disturbance in those habitats [155]. However, data reported by Carswell et al [49] for this species in treeless stands in New Zealand show high growth maintained even beyond 15 years, which could be related to a niche shift, or simply due to the short time interval explored.…”
Section: Biomass Accumulation and Mean Annual Increment (Mai)supporting
confidence: 84%
“…Common gorse has an annual rate of 100–200 kg ha −1 nitrogen accumulation during the rapid dry-matter accumulation period (Galappaththi et al ., 2022). In fact, U. europaeus has traditionally been used as a natural agricultural fertilizer due to its nutritive effect (Atlan et al ., 2015). Soil nitrogen not only favor plant growth, but also plant germination (Duermeyer et al ., 2018), which can explain the small negative effects or the absence of them that we found on the germination of the target species exposed to U. europaeus mulch.…”
Section: Discussionmentioning
confidence: 99%
“…Mulch for the experiments was prepared using dried branches, thorny twigs and phyllodes from U. europaeus , that were cut in fractions (c.a. 2 cm) to simulate the crushing or chopping process traditionally carried out by an electric fodder cutter after U. europaeus remotion for agricultural application (Jamil et al ., 2009; Atlan et al ., 2015; Khan et al ., 2016). Also, as a spiny shrub, U. europaeus would be difficult to farmers to handle if it is not cut.…”
Section: Methodsmentioning
confidence: 99%